Use of intraoperative ultrasound in resection of early-stage borderline ovarian tumors: A case series - Karthiga Natarajan; Marilyn Boo; Samir A. Saidi (Gynecologic Oncology Reports)
Borderline ovarian tumors (BOTs) commonly occur in women of reproductive age. For patients desiring fertility preservation, cystectomies are recommended as healthy ovarian tissue is spared. However, intraoperative identification of small BOTs can be challenging. Intraoperative ultrasound is a novel technique that enhances the visualization of anatomical structures, potentially allowing for a more precise excision of the ovarian lesion, which maximizes the preservation of healthy ovarian tissue. Although it has clear advantages, the literature on the use of intraoperative ultrasound in gynecological surgeries remains limited.Cases: We describe a case series of four women aged between 20 and 33 years old who underwent ultrasound-guided laparoscopic cystectomy for early-stage BOTs.Discussion: We demonstrate that intraoperative ultrasound in laparoscopic resection of early-stage BOTs improves visualization of the ovarian tissue, thereby minimizing the amount of healthy ovarian tissue excised, which optimizes fertility preservation in patients.